Correcting GPS coordinates in Apple iPhone - Dellytania Setiawan (2012)
The use of smartphone is growing rapidly. It leads to high demand for useful application in people’s life. Positioning is the common feature that people use in smartphone. Many positioning applications have been developed, for example GPS assisted map navigation, location-aware social networking, etc. However, GPS coordinates obtained from the GPS receiver in the smartphone is prone to errors. The most common reason is due to obstruction of tall building that results in weak signal strength at GPS receiver. This might affect the accuracy of GPS coordinates. GPS coordinates system is estimated to have up accuracy between 4 and 40 meters in the clear view of the sky.